Fabrication of CuO/MoO3 p-n heterojunction for enhanced dyes degradation and hydrogen production from water splitting. (22nd April 2022) - Hussain, Muhammad Khalid; Khalid, N.R.; Tanveer, Muhammad; Kebaili, Imen; Alrobei, Hussein
Abstract: The development of excellent photocatalytic material is highly required for energy and environmental applications. In this study, visible light responsive p-n heterojunction photocatalysts based on CuO/MoO3 with varying ratios of CuO were prepared by the facile hydrothermal method. The crystalline structure, surface morphology, chemical compositions and optical properties of the synthesized photocatalysts were studied using X-ray powder diffraction (XRD), scanning electron microscopy (SEM), Energy-dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), photoluminescence (PL) techniques and UV–Vi's absorption spectroscopy. The results showed that the 5%CuO/MoO3 nanocomposite displayed enhanced photocatalytic performance for the production of hydrogen (98.5 μmol h −1 g −1 ) and degradation of dyes rhodamine B (RhB) and alizarine yellow (AY) than all other samples. Furthermore, 5% CuO/MoO3 composite exhibited excellent stability after five consecutive cycles for both RhB and AY dyes. Overall, the improved photocatalytic performance of 5%CuO/MoO3 composite was due to increased adsorption of visible light, good surface morphology, enhanced charge separation/transfer which inhibited recombination of electrons and holes. This study could encourage the synthesis of novel and effective p-n heterojunction photocatalysts for practical applications. Highlights: CuO/MoO3 p-n heterojunction photocatalyst was prepared by hydrothermal method. Prepared CuO/MoO3 photocatalyst showed superior performance under visible light. The improved photocatalytic activity was due to synergistic effects of both materials.